2010
DOI: 10.1159/000280385
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Agent N-Acetyl Cysteine Exacerbates Endotoxin-Induced Hypoxemia and Hypotension and Induces Polycythemia in the Ovine Fetus

Abstract: Background: Lipopolysaccharide (LPS) delivered acutely to the ovine fetus induces cerebral white matter injury and brain inflammation. N-acetyl cysteine (NAC) is potentially neuroprotective as it blocks the production of inflammatory cytokines and increases glutathione levels; however, it is unknown whether NAC affects the physiological status of the fetus already exposed to an inflammatory environment. Objectives: Our objective was to determine whether NAC influences the physiological effects of LPS exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
1
10
1
Order By: Relevance
“…The beneficial effect of NAC could therefore be in part depends on this property. Although it has been reported evidence of NAC-induced vasodilation and hypotension [39,40], we didn’t found any systemic effect of NAC in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…The beneficial effect of NAC could therefore be in part depends on this property. Although it has been reported evidence of NAC-induced vasodilation and hypotension [39,40], we didn’t found any systemic effect of NAC in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…2a–c), which is supported by other reports showing that NAC improved survival of offspring after LPS injection in rat dams at GD16-183651, provided protection against fetal death and preterm labor induced by maternal inflammation33, and lowered the inflammatory cytokine response in amniotic fluid and placenta in rats3537. A previous publication reported that NAC has potential life-threatening effects on a fetus that has been exposed to endotoxins, which worsens LPS-induced fetal hypoxemia and hypotension52. However, our data show no reduction of hemoglobin and erythrocyte levels when NAC is administered (Table 1).…”
Section: Discussionsupporting
confidence: 66%
“…127 However, there are some concerns that N-acetylcysteine may compromise fetal cardiovascular stability and to date, no large clinical trials have evaluated systemic N-acetylcysteine administration in newborn infants - or their mothers - prior to delivery. 128 …”
Section: Potential Future Interventions To Reduce Bacteraemia-associamentioning
confidence: 99%